Language acquisition in Autism Spectrum Disorder: Strategies for early diagnosis and intervention – A review of literature (Research, Society and Development, 2023)
Autism Spectrum Disorder (ASD) is characterized as a neurodevelopmental disorder, with deficits in communication and social interaction with a defined diagnostic criteria. Although the main diagnosis is made by the pediatric neurologist and/or the psychiatrist, the clinician ability to refer children with a suspected condition, based on language differences to their neurotypical peers, is crucial for shortening the diagnosis time.  Because it is a neurodevelopmental condition, the earlier the interventions, the better the responses and prognosis in development. In this literature review, we aim at an updated discussion about the role of ASD on the child brain, the language development differences in neurotypical and ASD children, the emerging early diagnosis technologies, and the early intervention therapies available for verbal and non-verbal ASD children’s, as well as adults, with a final focus on music therapy.